Stress fractures in athletes - Ferry, A. T.; Graves, T.; Theodore, G. H.; Gill, T. J. (The Physician and Sportsmedicine, 2010)
Abstract: Stress fractures that occur in the young active population typically represent an overuse injury, and may lead to prolonged periods of restriction from play if they are not treated appropriately. Several risk factors have been identified and must be addressed when treating these patients. Low-risk stress fractures can be successfully treated with activity restriction and a stepwise return to sport. Several pharmacologic and nonoperative treatment modalities have been described. However, high-risk stress fractures are more difficult to treat because they may have an increased rate of delay and nonunion, and often require surgical stabilization. When treating an athlete with a stress fracture, the objective is a safe and quick return to sport; therefore, special considerations must be made in this population, particularly when dealing with the in-season athlete.